Nanoalloy platinum infiltrated BSCF cathode for enhancement of intermediate temperature solid oxide fuel cell. - Ab Ghani, Sulaiman (Universiti Sains Malaysia, 2014)

(untitled)
A new Bao.sSro.sCoo.sFeo.203-15 (BSCF) based composites electrodes for electroreduction of oxygen was developed. The synthesis of pure BSCF using citrate-EDTA complexing method was carried out at different pHs of which pH 9 was the best. The BSCF-MWCNT composites electrode was prepared as pastes and modified glassy carbon electrodes (GCE) by chemical deposition and in situ mechanical mixing. In the pastes type the inclusion and the uniform dispersal of MWCNT within BSCF were confirmed by XRD and SEM studies.